2017
DOI: 10.3390/electronics6040086
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Properties of Plasma-Deposited Thin Films Derived from Pelargonium graveolens

Abstract: Abstract:Inherently volatile at atmospheric pressure and room temperature, plant-derived precursors present an interesting human-health-friendly precursor for the chemical vapour deposition of thin films. The electrical properties of films derived from Pelargonium graveolens (geranium) were investigated in metal-insulator-metal (MIM) structures. Thin polymer-like films were deposited using plasma-enhanced synthesis under various plasma input power. The J-V characteristics of thus-fabricated MIM were then studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It has been shown that fabricating geranium plasma polymers at higher power leads to an increase in the degree of cross-linking, and potentially rise resistance against deformation 45 . The resultant polymers become harder and more rigid owing to the increase in the bonding interconnection and dense chain packing 79 . Here, we assumed that the increase in the bonding interconnection degree would curb/restrain the freeing of nanoparticles from the films fabricated at 50 W. ICP data also suggested that a higher concentration of ZnO was released from surfaces of ZnO/Ge 10 W, making it significantly more antibacterially effective than ZnO/Ge 50 W that showed a low degree of release hence, much lower antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that fabricating geranium plasma polymers at higher power leads to an increase in the degree of cross-linking, and potentially rise resistance against deformation 45 . The resultant polymers become harder and more rigid owing to the increase in the bonding interconnection and dense chain packing 79 . Here, we assumed that the increase in the bonding interconnection degree would curb/restrain the freeing of nanoparticles from the films fabricated at 50 W. ICP data also suggested that a higher concentration of ZnO was released from surfaces of ZnO/Ge 10 W, making it significantly more antibacterially effective than ZnO/Ge 50 W that showed a low degree of release hence, much lower antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the fitting of ln J vs. ln V for all manufactured polymer and composites demonstrates a similar behavior as those in ln J vs. V 1/2 . By observing power law index rates and the linear fitting of the J–V plots for pristine polymer that was previously reported in [37], the Schottky mechanism could specifically dominate the charge transport of geranium polymers in the higher field region. It suggests that the ZnO NPs did not significantly affect the transport at high fields, but may indirectly change the carrier transport properties at lower fields.…”
Section: Resultsmentioning
confidence: 63%
“…The optical band gap decreased slightly from 3.67 to 3.60 eV for higher plasma powers, which was explained by the increased presence of dangling chains that might lead to formation of additional intermediate energy levels and/or defects decreasing the optical band gap. [89] Hennekam et al analyzed the fragmentation occurring in the plasma phase during PECVD of sandalwood oil at reduced pressure and 2-50 W RF power. The gas phase was characterized using mass spectrometry (MS) and optical emission spectroscopy (OES), while the resulting films were characterized with X-ray photoelectron spectroscopy (XPS), Time-of-flight Secondary Ion MS (ToF-SIMS) and atomic force microscopy (AFM).…”
Section: Pecvd Of Biogenic Precursors 21 | Pecvd Of Essential Oilsmentioning
confidence: 99%